Hierarchical pattern recognition method with the multi-level distance function - CHMIELEWSKI, L.J.; KOSIŃSKI, W. (Engineering Transactions, 1990)
To overcome the disadvantages of the conventional distance pattern recognition method, based on the distance function of a complicated form, it is proposed to introduce a set of simpler functions which form a multi-level distance function. The resulting recognition method consists in gradual elimination of the classes to which a recognized object does not belong. The proposed, very simple algorithm operates in such a way as if in the set of classes there existed a hierarchy which would make it possible to exclude subsequently the whole groups of classes; however, such hierarchy is not introduced. It is (implicitly) comprised in the structure of the recognition algorithm. This provides for a significant reduction of the execution time. The algorithm has been applied to object recognition in computer vision, where the requirement of large calculation speed is particularly important.